Central Nervous System Blastomycosis With Multiple Brain Abscesses Presenting as Right Upper Extremity Weakness. (October 2019) - Ryan, Dylan; Lippert, William C.; Fenwick, Alexander J.; Bhatt, Mahesh; Jones, Charles R.
Blastomycosis is a mycotic infection that typically affects the lung, but that can have dermatologic, orthopedic, genitourinary, and central nervous system manifestations. Blastomyces dermatitidis is a true human pathogen, which can produce disease in immunocompetent hosts. Risk factors for infection include residence in or travel to endemic areas and outdoor occupation, particularly those activities near open bodies of water and that disrupt soil. Immunosuppressed patients are also at increased risk for severe and disseminated disease. We present a case of a 79-year-old male who presented with a 2-week history of progressive right upper extremity weakness and severe odontogenic disease. He was found to have multiple brain abscesses with positive cultures from a cerebral abscess incision and drainage for B dermatitidis . He underwent an incision and drainage of the largest cerebral abscess and was treated with intravenous liposomal amphotericin B, which he tolerated poorly. He was subsequently switched to voriconazole, which was well tolerated, and his neurological deficits improved throughout his hospitalization.